1978
DOI: 10.1073/pnas.75.7.3254
|View full text |Cite
|
Sign up to set email alerts
|

Cole-Moore effect in the frog node.

Abstract: Potassium currents were recorded from the voltage-clamped frog node (Rana esculenta) during various test pulses that followed hyperpolarizing prepulses of different amplitudes and durations. Both the delay in potassium current onset and the shape of the current trace as a function of time were found to be a function of prepulse parameters. This finding is different from the current trace superposition described by Cole and Moore for a specific test pulse, sodium equilibrium potential in the squid giant axon. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Frankenhaeuser and Hodgkin (66) had found that the sigmoid shape of the K current in squid axon was exaggerated by hyperpolarizing pulses applied just before a depolarizing step: the greater the conditioning hyperpolarization, the greater the apparent delav in the rise of the K current. This phenomenon has been observed in a number of channel ionic currents, including frog node of Ranvier (75,ZOZ), crayfish axons (226), and pheochromocytoma (PC-12) cells (120), as well as in the gating currents from squid axon (23) and Shaker K channels (22). Although n4 schemes do predict such a phenomenon (see Fig.…”
Section: B Anomalous Kinetic Observationsmentioning
confidence: 89%
“…Frankenhaeuser and Hodgkin (66) had found that the sigmoid shape of the K current in squid axon was exaggerated by hyperpolarizing pulses applied just before a depolarizing step: the greater the conditioning hyperpolarization, the greater the apparent delav in the rise of the K current. This phenomenon has been observed in a number of channel ionic currents, including frog node of Ranvier (75,ZOZ), crayfish axons (226), and pheochromocytoma (PC-12) cells (120), as well as in the gating currents from squid axon (23) and Shaker K channels (22). Although n4 schemes do predict such a phenomenon (see Fig.…”
Section: B Anomalous Kinetic Observationsmentioning
confidence: 89%
“…Somewhat more complicated results have been obtained by Ganot et al (1978) with varying prepulse duration. Our unpublished calculations, analogous to those described above, show that the model proposed could account for most of their results; furthermore, x I = x H = 4 were found to give the best fit.…”
Section: K Currents At Depolarization: Analysismentioning
confidence: 92%
“…However, this raises serious difficulties for interpreting in physical terms the molecular events underlying the changes in permeability. Alternatively, it can be accounted for according to three interpretations: (i) the K+ conductance is determined by a multi-state process; (ii) the K+ conductance is determined by two or more types of K+ channels; (iii) the K+ current is affected by some extra axonal parameters (Ganot et al 1978). In this paper and the following (Dubois, 1981), several arguments are presented which support these interpretations.…”
mentioning
confidence: 83%